Species distribution and antibiotic resistance of Shigella isolates in an urban community in Malaysia - Lee, W.S.; Puthucheary, S.D. (2003)
There is an increasing trend for Shigella isolates worldwide to be resistant to commonly prescribed antibiotics. The species distribution and antibiotic resistance of Shigella species isolated from children in Kuala Lumpur, Malaysia from 1978 to 1997 was reviewed. Three hundred and eighty six isolates were positive for Shigella species, representing 1.4 (95 CI: 1.3-1.6) of the 26320 total stool specimens and 13 (95 CI: 11.8-14.2) of 2986 isolates positive for bacterial pathogens. Shigella flexneri, constituting 74 of all isolates in the first five years of the study, decreased by 40 during the last five years (95 CI of decrease: 22.1-57.9), p-value < 0.0001) to 34. There was a significant reduction (chi2 for linear trend = 77.6, p-value < 0.001) in the number of Shigella isolates as a percentage of total stool isolates obtained. 58 of the 241 isolates tested for antibiotic sensitivity were resistant to at least one antibiotic, and 42 wEre multi-resistant to three or more antibiotics. Shigella species was not a common pathogen among children admitted with diarrhoea in Kuala Lumpur, and was more likely to be resistant to commonly prescribed antibiotics.